Evaluación de las variables del marketing mix como contribución a la gestión comercial en la dulcería y restaurante El Regocijo - Rodríguez Delgado, Jean Carlos (2019)
The objective of this research was to evaluate the variables of marketing mix as a contribution to commercial management in the candy store and the Regocijo restaurant, located in Bolivar canton, Manabí. Four methodological phases were structured, in the first phase the variety of products currently offered by the candy shop was identified, as well as an analysis of the micro-environmental and macro-environmental factors of the microenterprise to analyze the political, economic, social and technological factors. In the second phase, marketing channels were determined, market segmentation was started, the competitive profile matrix was developed, where the most important competitors of Calceta city were identified. What refers to the third phase is the development of an advertising and promotion plan and its budget, identifying resources, times, costs, among others. In the last phase, a plan of actions was designed, including strategies, activities, responsible parties, timing and compliance indicators that contribute to strengthening the shortcomings in the investigation. It was concluded that the products destined to the sale of the candy store an restaurant El Regocijo are: starch cookies, coconut cookies, alfajor, troliche, sighs, huevo mollo, biscochuelo, rompope, manjar, custard and its star products are rolled and assorted sweets, like the microenterprise, carries out the sale and marketing through two types of marketing channels such as direct and retail.